Regulation of Virulence by Two-Component Systems in Pathogenic Burkholderia - Schaefers, Matthew M. (Infect Immun, 2020)
The regulation and timely expression of bacterial genes during infection is critical for a pathogen to cause an infection. Bacteria have multiple mechanisms to regulate gene expression in response to their environment, one of which is two-component systems (TCS). TCS have two components. One component is a sensory histidine kinase (HK) that autophosphorylates when activated by a signal. The activated sensory histidine kinase then transfers the phosphoryl group to the second component, the response regulator, which activates transcription of target genes. The genus Burkholderia contains members that cause human disease and are often extensively resistant to many antibiotics. The Burkholderia cepacia complex (BCC) can cause severe lung infections in patients with cystic fibrosis (CF) or chronic granulomatous disease (CGD). BCC members have also recently been associated with several outbreaks of bacteremia from contaminated pharmaceutical products. Separate from the BCC is Burkholderia pseudomallei, which is the causative agent of melioidosis, a serious disease that occurs in the tropics, and a potential bioterrorism weapon. Bioinformatic analysis of sequenced Burkholderia isolates predicts that most strains have at least 40 TCS. The vast majority of these TCS are uncharacterized both in terms of the signals that activate them and the genes that are regulated by them. This review will highlight TCS that have been described to play a role in virulence in either the BCC or B. pseudomallei. Since many of these TCS are involved in virulence, TCS are potential novel therapeutic targets, and elucidating their function is critical for understanding Burkholderia pathogenesis.